Epidemiological implications of the spectrum of resistance to rice blast - Sang Won Ahn; Ou, SH (1982)
The infection efficiency and the infection rate of the spore population of Pyricularia oryzae was lower if the percentage of races to which each cultivar was resistant was high. It appears that cultivars with resistance to a high percentage of the races of the pathogen behaved as expected for “horizontal” or “general” resistance.